A Decade of Muricatacin Synthesis and Beyond. Issue 44 (11th August 2020) - Fernandes, Rodney A.; Gangani, Ashvin J.; Kumari, Anupama; Kumar, Praveen
Abstract : In this review, we have abstracted the various syntheses of both enantiomers of muricatacin (a member of a bigger class of acetogenins, ACGs), over the last decade (2010–2020). Developments in the synthesis of various epimers, homologues, oxa‐analogues, δ‐lactones, and the furofuranone analogues are also enfolded in this review. Most of the synthesis involve chiral pool and catalytic enantioselective approaches, while a few are hinged on the use of chiral auxiliary and resolution methods. Muricatacin with orthogonally differentiated two oxy‐functions also serve as a start point in the synthesis of higher molecules of the acetogenin family, for example, cis ‐solamins, and these have also been covered herein. Abstract : Various syntheses of both the muricatacin enantiomers and analogues adopting different strategies in the last decade are described in this review. Additionaly, the strategic use of muricatacin as starting point in synthesis of reticulatacin, cis ‐solamins and giganin is covered.